Listening to Music as a Means of Relaxation and Concentration - Kolenko, Minea (Širjenje obzorij o poučevanju glasbe, 2025)
Listening to music positively impacts mood, motivation, and concentration, leading to improved cognitive processes. Music can enhance memory, confidence, and focus, as demonstrated in school settings. Additionally, music has therapeutic effects, helping to reduce stress and anxiety and improve overall well-being. Music training also enhances language skills, as music and language engage similar areas of the brain. Musical activities such as singing, dancing, and performing musical stories stimulate children's cognitive and language development as well as their social interaction. Thus, music influences not only psychological well-being but also motor and language functions.